2018
DOI: 10.1177/0020764018784624
|View full text |Cite
|
Sign up to set email alerts
|

Media reporting of suicide and adherence to media guidelines

Abstract: Overall, adherence to media guidelines on reporting suicide in Ireland improved in certain key areas from September 2009 until December 2012. Nonetheless, important challenges remain. Increased monitoring by media monitoring agencies, regulators and government departments is required. Implementation should be conducted using a pro-active approach and form part of the curriculum of journalists and editors. The inclusion of guidelines for the reporting of suicidal behaviour in press codes of conduct for journali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
28
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 46 publications
6
28
0
2
Order By: Relevance
“…In spite of the wide dissemination and promotion of WHO guidelines for media suicide reporting, most studies report a generally low reported adherence to guidelines and show 10 cultural differences in compliance with various guideline items [16][17][18][19][20][21][22][23][24]. For instance, some countries reported a quite low adherence to providing helpful information and higher adherence with not publishing photographs.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the wide dissemination and promotion of WHO guidelines for media suicide reporting, most studies report a generally low reported adherence to guidelines and show 10 cultural differences in compliance with various guideline items [16][17][18][19][20][21][22][23][24]. For instance, some countries reported a quite low adherence to providing helpful information and higher adherence with not publishing photographs.…”
Section: Discussionmentioning
confidence: 99%
“… Media reporters can add context to individual incidents by referring to the whole spectrum of sexual violence, reporting data on the prevalence of sexual violence and related issues in that region, counteracting myths and outdated attitudes and also contacting experts to educate the readers/viewers. ( “Reporting on Sexual Violence,” 2013 ) Frame country specific media guidelines for sensitive reporting of GBV and crimes – Given the positive impact of framing media guidelines for reporting suicide,( McTernan et al, 2018 ) a similar approach may be followed with regard to media reporting of GBV; guidelines already available ( Global Protection Cluster (GPC), 2014 ) may be adapted for use by countries. Mention about consequences to the perpetrators of violence – Media must highlight the legal and social consequences of the act on the perpetrator(s) and their family members.…”
mentioning
confidence: 99%
“…Frame country specific media guidelines for sensitive reporting of GBV and crimes – Given the positive impact of framing media guidelines for reporting suicide,( McTernan et al, 2018 ) a similar approach may be followed with regard to media reporting of GBV; guidelines already available ( Global Protection Cluster (GPC), 2014 ) may be adapted for use by countries.…”
mentioning
confidence: 99%
“…CMAJ readers will probably be interested to know that suicidal behaviour and contagion fuelled by media reporting (Werther v. Papageno effect) are also currently being investigated in many other countries, such as Austria, Germany, China, India, the United Kingdom, Ireland and Sri Lanka. [2][3][4][5][6][7] For example, in German-speaking countries, when the term "free death" (in German: Freitod) is used in the news instead of the terms "suicide" (in German: Suizid) or "self-murder" (Selbstmord), readers seem to have a greater understanding of suicide among individuals with incurable diseases. 2 However, suicidal persons do not make a free, rational decision that the term "free death" supposedly implies (i.e., an emotional tunnel vision of one's own life and environment).…”
mentioning
confidence: 99%
“…1 Unfortunately, most newspapers and online publications do not yet follow the principles of good media reporting of suicides, as the current data show. [3][4][5]7,9 Martin Hofmeister PhD Nutritional scientist, Department Food and Nutrition, Consumer Centre of the German Federal State of Bavaria, Munich, Germany n Cite as: CMAJ 2018 December 10;190:…”
mentioning
confidence: 99%